A DFT study on the mechanism and regioselectivity of NHC-catalyzed double acylation of aromatic 1, 2-diketones with α, β-unsaturated ketones. (24th August 2022) - Luo, Jing; Han, Li-Li; Chen, Kuohong; Song, Jinshuai; Wei, Donghui
Abstract : The possible mechanisms and the origin of regioselectivity of the N-heterocyclic carbene (NHC)-catalyzed double acylation reaction of aromatic 1, 2-diketones with α, β-unsaturated ketones have been theoretically studied using density functional theory. Abstract : The possible mechanisms and the origin of regioselectivity of the N-heterocyclic carbene (NHC)-catalyzed double acylation reaction of aromatic 1, 2-diketones with α, β-unsaturated ketones have been theoretically studied using density functional theory. Two regioselective pathways associated with the attack on the acetyl carbon or benzoyl carbon by NHC have been discovered, and the attack pathway to the acetyl carbon has been identified as the main pathway. The most energetically favorable pathway has been confirmed to contain several steps: nucleophilic addition of NHC, intramolecular migration of the p -chlorobenzaldehyde group, Michael addition of functional enamine to ketene, the formation of a five membered ring, and dissociation of NHC. The Michael addition forming a C–C bond is the rate-determining step. Moreover, the origin of regioselectivity has also been explored based on the detailed mechanistic cycle and the analyses of local electrophilic and nucleophilic indexes.